Attitude towards Information and Communication Technology Use among University Teachers of different Faculties in Relation to Computer Anxiety - Mehra, Vandana; Far, Ziba Nikkah (INDIAN EDUCATIONAL REVIEW, 2015)
The rapid growth in computer-based Information and Communication Technology (ICT) has created new opportunities for universities to manage teaching and training differently and more effectively. The present study was conducted on 200 university teachers’ attitude towards ICT use belonging to different faculties and at different levels of computer anxiety. Two tools were used for data collection, viz., Scale of Attitude towards Information and Communication Technology use and Computer Anxiety Scale. The main findings of the study were: (i) There was no difference between attitude towards Information and Communication Technology use among university teachers of different faculties, and (ii) Teachers with low, moderate and high computer anxiety exhibited difference in their attitude towards Information and Communication Technology use. Teachers with low computer anxiety exhibited better attitude towards Information and Communication Technology use as compared to those with moderate and high levels of computer anxiety.